Defending the guilty : truth and lies in the criminal courtroom / Alex McBride. - McBride, Alex (Penguin Books, 2011)
Every day, like every criminal barrister in this country, Alex McBride stands up in court and, with nothing but his hard-won legal expertise, attempts to save people from criminal conviction and even a lifetime behind bars. In this memoir he takes us behind the scenes of Britain's criminal justice system.